Update in the certification of endometriosis centers Neues in der Zertifizierung von Endometriosezentren - Schaefer, Sebastian D.; Sillem, Martin; Schweppe, Karl-Werner; Burghaus, Stefanie; Beckmann, Matthias (Gynäkologe, 2021)
Endometriosis is among the most frequent diseases of women during reproductive age. The disease itself but also its treatment significantly impairs quality of life. Top-level specialized centers have been established to ensure diagnosis and treatment. The certification process defined by Stiftung Endometriose-Forschung (SEF), European Endometriosis League (EEL) and patient self-help organisations is intended to guarantee comparable quality. Diagnosis and treatment need to be based on current guidelines. The redefinition of the term center by the German Gemeinsame Bundesausschuss (G-BA) has made it necessary to adapt the established staging concept. In the future specialized “endometriosis practices”, “endometriosis units” and “endometriosis centers” will be certified according to predefined criteria.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Guidelines; Integrative medicine; Quality of life; Reproduction; Shared decision making